2005
DOI: 10.1007/s10525-005-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Endogenous Opioid System to Regulation of Heart Resistance to the Arrhythmogenic Effect of Short-term Ischemia and Reperfusion

Abstract: Preliminary selective blockade of µ , δ 1 , δ 2 , κ 1 , and κ 2 opioid receptors proved to have no effect on the incidence of ventricular arrhythmias during a 10-min coronary occlusion and subsequent reperfusion in ketamine-anesthetized rats. We propose that the endogenous opioid system has no considerable role in regulation of heart resistance to the arrhythmogenic effect of short-term local ischemia and subsequent reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The selective δ 1 -OR antagonist, BNTX (7-benzylidenenaltrexone maleate), was given at a dose of 0.7 mg/kg (Maslov et al, 2009;Sofuoglu et al, 1993), and the selective δ 2 -OR antagonist, naltriben mesylate, was used at a dose of 0.3 mg/kg (Maslov et al, 2009;Kamei et al, 1995). The selective κ-OR antagonist, nor-binaltorphimine (nor-BNI), was administered at a dose 9 mg/kg (Birch et al, 1987;Maslov et al, 2005aMaslov et al, , 2005b. The selective μ-OR inhibitor, CTAP (NH 2 -D-Phe-c[Cys-Tyr-D-Trp-Arg-Thr-L-Pen]-Thr-NH 2 ), was used at a dose of 0.1 mg/kg based on our preliminary experiments.…”
Section: Opioid Receptor Antagonistsmentioning
confidence: 99%
“…The selective δ 1 -OR antagonist, BNTX (7-benzylidenenaltrexone maleate), was given at a dose of 0.7 mg/kg (Maslov et al, 2009;Sofuoglu et al, 1993), and the selective δ 2 -OR antagonist, naltriben mesylate, was used at a dose of 0.3 mg/kg (Maslov et al, 2009;Kamei et al, 1995). The selective κ-OR antagonist, nor-binaltorphimine (nor-BNI), was administered at a dose 9 mg/kg (Birch et al, 1987;Maslov et al, 2005aMaslov et al, , 2005b. The selective μ-OR inhibitor, CTAP (NH 2 -D-Phe-c[Cys-Tyr-D-Trp-Arg-Thr-L-Pen]-Thr-NH 2 ), was used at a dose of 0.1 mg/kg based on our preliminary experiments.…”
Section: Opioid Receptor Antagonistsmentioning
confidence: 99%
“…This agrees with previously published results of our investigations, which showed that opioid receptor antagonists had no effect on the incidence of occlusion and reperfusion-induced arrhythmias in rats. 12 This fact indicates that endogenous opioids do not regulate cardiac tolerance to the arrhythmogenic effects of ischemia and reperfusion in nonadapted rats. However, our data contradict the results of other investigators who found antiarrhythmic effects of opioid receptor antagonists during cardiac ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that all above-mentioned investigators performed their experiments with animals anesthetized with barbiturates, while we used chloralose or ketamine as anesthetics. 12 It should be noted that cardiovascular system response to IV-administered enkephalins is directly opposite in dogs anesthetized with barbiturates and chloralose. 30 Perhaps opioid receptor antagonists exhibited antiarrhythmic properties only in animals anesthetized with barbiturates but not chloralose or ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations